Fathead Minnows Exposed to Organic Compounds from Oil Sands Tailings as Embryos Have Reduced Survival, Impaired Development, and Altered Behaviors That Persist into Larval Stages. (11th April 2022) - Reynolds, Jessie S.; Jackson, Brianna L.; Madison, Barry N.; Elvidge, Chris K.; Frank, Richard A.; Hasler, Caleb T.; Headley, John V.; Hewitt, L. Mark; Peru, Kerry M.; Yakimowski, Sarah B.; Orihel, Diane M.
Abstract: Our study evaluated whether exposure to naphthenic acid fraction compounds (NAFCs) extracted from oil sands process–affected waters (OSPW) has adverse effects on fish embryos that persist into later life. We exposed fathead minnow ( Pimephales promelas ) embryos to concentrations of NAFCs found in OSPW (2.5–54 mg/L) for 7 days (1 day postfertilization to hatch), then raised surviving larvae in outdoor mesocosms of uncontaminated lake water for 1 month. Embryos exposed to NAFCs were more likely to exhibit malformations (by up to 8‐fold) and had slower heart rates (by up to 24%) compared to controls. Fish raised in uncontaminated lake water following exposure to NAFCs as embryos, were 2.5‐fold less likely to survive during the larval stage than control fish. These fish also showed up to a 45% decrease in swim activity and a 36% increase in swim burst events during behavioral tests relative to controls. We conclude that exposure to NAFCs during the embryonic stage can have lasting effects on fish survival, physiology, and behavior that persist at least through the larval stage. These findings of delayed mortalities and persistent sublethal effects of embryonic NAFC exposure are relevant to informing the development of regulations on treated OSPW releases from mining operations. Environ Toxicol Chem 2022;41:1319–1332. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : Embryonic exposure of fathead minnows ( Pimephales promelas ) to naphthenic acid fraction components derived from oil sands tailings in a seminatural setting had adverse effects on survival, development, and behavior that persisted into larval stages. NAFC = naphthenic acid fraction component.